1994
DOI: 10.1042/bj3030625
|View full text |Cite
|
Sign up to set email alerts
|

Glucose modulates the binding activity of the β-cell transcription factor IUF1 in a phosphorylation-dependent manner

Abstract: In the human insulin gene, three regulatory sequences upstream of the transcription start site at -77 (the CT1 box), -210 (the CT2 box), and -315 (the CT3 box) bind a beta-cell-specific transcription factor, IUF1. Recent studies have mapped a glucose response element to a CT-like sequence in the rat insulin I gene. The present study was therefore undertaken to ascertain the role of IUF1 in glucose-stimulated insulin gene transcription. IUF1-binding activity was measured by electrophoretic mobility shift assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
1
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(95 citation statements)
references
References 34 publications
3
90
1
1
Order By: Relevance
“…For example, phosphorylation of PDX-1 in glucose-induced ␤ cells appears to stimulate its DNA binding activity (25,26,35). In addition, RIPE3b1 binding activity is reduced by CIAP and BPP treatment, suggesting that activation of this insulin gene transcription factor is also mediated by phosphorylation, specifically of the 46-kDa DNA binding subunit (9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, phosphorylation of PDX-1 in glucose-induced ␤ cells appears to stimulate its DNA binding activity (25,26,35). In addition, RIPE3b1 binding activity is reduced by CIAP and BPP treatment, suggesting that activation of this insulin gene transcription factor is also mediated by phosphorylation, specifically of the 46-kDa DNA binding subunit (9).…”
Section: Resultsmentioning
confidence: 99%
“…RIPE3b1 DNA binding is mediated by a ␤ cellenriched protein(s) of ϳ46 kDa, whose activity is reduced by either calf intestinal alkaline phosphatase (CIAP) 1 or a brainenriched phosphatase preparation (BPP) treatment (9). These results suggested that RIPE3b1 binding is regulated by phosphorylation, a posttranslational modification mechanism also utilized in controlling PDX-1 activation (25,26). In an effort to more fully understand the role that phosphorylation plays in RIPE3b1 function, we have characterized the phosphatase activity that affects RIPE3b1 binding within the ␤ cell.…”
mentioning
confidence: 82%
“…In contrast to the relatively slow glucose-induced increase in bHLH heterodimer binding to the E element, PDX-1 binding increases acutely in response to a rise in glucose concentration (26,29). The glucose-stimulated increase in DNA binding by PDX-1 is reportedly due to phosphorylation that is dependent on phosphatidylinositol 3-kinase and the p38 MAP kinase (26,30), although neither kinase was found to directly phosphorylate PDX-1. Glucose also causes PDX-1 to shift into the nucleus (31,32) and increases its transcriptional activation capacity (33).…”
mentioning
confidence: 86%
“…A elements bind any of several homeodomain transcription factors found in ␤ cells, the most abundant being PDX-1 (25)(26)(27)(28). In contrast to the relatively slow glucose-induced increase in bHLH heterodimer binding to the E element, PDX-1 binding increases acutely in response to a rise in glucose concentration (26,29).…”
mentioning
confidence: 97%
“…Insulin promoter factor 1 (IPF-1) (also known as STF-1, IDF-1, IDX-1, and PDX-1) is a homeodomain transcription factor that is absolutely required for the development of the pancreas (8,9) and also mediates glucose-responsive stimulation of insulin gene transcription (10)(11)(12)(13)(14)(15). IPF-1 is also implicated in the transcriptional regulation of other key ␤-cell specific genes, including GLUT2 (16), islet amyloid polypeptide (17,18), and glucokinase (19).…”
Section: Impaired Insulin Secretion and Increased Insulin Sensitivitymentioning
confidence: 99%